3D printing of boxfish and its drag studies - Goh, Yu Jie (2019)
This report examines the aerodynamics behaviour of a boxfish through studies of its topography and conducts computational simulations to obtain its drag coefficients. A scaled-up boxfish model was created through CAD drawing using SOLIDWORKS with 3D-printing carried out as well. The CAD model was then assessed through Computational Fluid Dynamics (CFD) with the help of ANSYS Workbench 19.1 where the drag coefficients were further validated through multiple simulations. The drag coefficient of the boxfish found have shown coherence with cases studies presented under similar conditions. Further exploration with the model was also conducted with respect to different angles of approach between itself and the fluid. These led to the conclusion of the need to include factors such as control surfaces to maintain the model at certain angle for ensuring favourable drag coefficient.